2021
DOI: 10.1002/ajoc.202100279
|View full text |Cite
|
Sign up to set email alerts
|

Pd‐Catalyzed Domino Cross‐Coupling: Synthesis of Functionalized 4‐(Arylethynyl)Coumarins

Abstract: A Pd-catalyzed domino cross-coupling methodology was developed to synthesize various 4-(arylethynyl) coumarin derivatives involving 4-(gem-dibromovinyl) coumarins and triarylbismuths as threefold aryl donor reagents. In these reactions, 4-(gem-dibromovinyl)coumarin derivatives have been cross-coupled with sub-stoichiometric amounts of triarylbismuth reagents. This study involving mono-, chemoselective and bis-couplings have been demonstrated with versatile reactivity under the established Pdcatalyzed domino co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The 4‐(arylethynyl)‐3‐bromocoumarins required for this study are prepared using the cross‐coupling method reported with 3‐bromo‐4‐( gem ‐dibromovinyl)coumarins and triarylbismuth reagents under palladium‐catalyzed conditions (Scheme 3) from our research group [12a] …”
Section: Resultsmentioning
confidence: 99%
“…The 4‐(arylethynyl)‐3‐bromocoumarins required for this study are prepared using the cross‐coupling method reported with 3‐bromo‐4‐( gem ‐dibromovinyl)coumarins and triarylbismuth reagents under palladium‐catalyzed conditions (Scheme 3) from our research group [12a] …”
Section: Resultsmentioning
confidence: 99%
“…In 2021, Maddali L. N. Presented a powerful [64] and convenient P‐coupled domino cross‐coupling methodology of a new type. This approach makes it possible to synthesize coumarin derivatives with 4‐(arylethynyl) substitutions, addressing the issue of diversity.…”
Section: Various Strategies For the Synthesis Of Polybeznocoumarinsmentioning
confidence: 99%
“…Coumarin dyes are widely used in uorescent probes because of their low biotoxicity, high uorescence sensitivity, good photostability and easy modi cation of the main chain [22][23][24][25][26][27][28][29][30] . Coumarin derivatives can also be used as uorescence markers or imaging agents to identify tumor lesions and study the subcellular localization of drugs [31][32][33][34][35][36][37][38][39][40][41][42] . In this paper, two novel uorescent probes were synthesized using coumarin with an aldehyde (CHO group) as the uorophore.…”
Section: Introductionmentioning
confidence: 99%